Traditional/Folk practices of Kerala Case studies- Part V: Healing Art of Tribal communities of Kerala - S Rajasekaran; T G Vinodkumar; M Navas (Journal of Traditional and Folk Practices (JTFP), 2017)
Traditional Knowledge (TK) plays an important role in the day-to-day life of tribal communities and it has become necessary to document, conserve and sustainably utilize this valuable knowledge for the benefit of Nature and its inhabitants as a whole. In this context, current studies carried out by Jawaharlal Nehru Tropical Botanic Garden and Research Institute (JNTBGRI) revealed that TK from the oral health tradition, especially the plants used for food and medicine in Kerala is fast disappearing. JNTBGRI has developed formats and prepared methodologies for the systematic documentation of TK associated with medicinal and food plants used by the different tribal communities of Kerala effectively. Prior Informed Consent (PIC) is also taken for the systematic documentation, before obtaining the TK from the knowledge providers/ holders/custodians with a view to implement Access and Benefit Sharing as per the Biological Diversity Act (2002) and Biological Diversity Rule (2004) in the true spirit.